Role of nitric oxide in septal coronary arteries of obese Zucker rats - Prathipati, Priyanka; Quadri, Syed; Jackson, Debra; Jackson, Keith (International Journal of Medicine, 2014)
Background: Metabolic syndrome is a collection of ailments resulting in a higher risk of cardiovascular disease and type II diabetes mellitus. It also results in prolonged endothelial dysfunction which promotes hypertension. Objective: The current study examines the acute effect of carbon monoxide (CO) inhibition and nitric oxide (NO) stimulation in septal coronary arteries. Methods: These studies were conducted in inactin anesthetized obese and lean Zucker rats (13-14 weeks of age). Coronary arteries were isolated from obese and lean Zucker rats and in vitro experiments were conducted.  Isolated coronary arteries were pre-treated with chromium mesoporphyrin (CrMP) which is a heme oxygenase inhibitor and L-arginine, a NO precursor. Results: Blood pressure, non-fasting blood glucose, HBCO, CO levels and Arginase I expression were higher in obese Zucker rats (ZR) as compared to the lean (L) group. Obese ZR had higher body, kidney and heart weights as compared to the LZR. Acetylcholine induced vasodilation was greatly attenuated in Obese ZR compared to the lean group. No differences in the diameters of the septal coronary artery were observed in both groups when treated with CrMP. However, pretreatment with L-arginine, abolished the differences between the groups. Conclusion: This study demonstrates the potential of NO induction to improve coronary blood flow during metabolic syndrome induced endothelial dysfunction, where alterations in CO levels appeared to have no significant coronary effects.   Keywords: Metabolic Syndrome, Endothelial Dysfunction, Hypertension, L-Arginine, Endogenous CO.